How can infectious diseases be prioritized in public health?: A standardized prioritization scheme for discussion - Krause, Gérard (EMBO reports, 2008)
The prevention and control of infectious diseases involves dealing with numerous pathogens, each of which poses a specific threat to public health. In order to rationally allocate the limited resources for research, surveillance and other activities, it is necessary to prioritize infectious diseases; how to do this is the dilemma that public-health experts face.